Menjelajahi Maqamat Spiritual: Kontribusi K.H. Juchran Erfan Ali terhadap Tasawuf dan Pendidikan Islam di Pondok Pesantren Ushuluddin Kabupaten Banjar - Paidillah Rijani; Rahmad Hidayat (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2024)
This study discusses the recitation of Sufism developed by K.H. Juchran Erfan Ali at the Ushuluddin Islamic Boarding School, Banjar Regency. The goal is to understand the form, pattern, and relevance of the teachings of Sufism taught to students in the context of contemporary Islamic spirituality and education. This research approach is qualitative with a type of field research, using observation techniques, in-depth interviews, and documentation of manuscripts by K.H. Juchran. The results of the study show that the recitation of Sufism in this pesantren integrates Sufism morally, practically, and philosophical in the framework of sharia. K.H. Juchran emphasizes the balance between dzahir and mind, and places the experience of ma'rifat as the peak of the spiritual journey that comes from the concept of Nur Muhammad. The novelty of this research lies in the identification and mapping of the teachings of Sufism by K.H. Juchran which displays a synthesis between philosophical Sufism and the educational practice of local Islamic boarding schools